In vitro embryo germination and callus induction of Cynometra cauliflora, an underutilized medicinal plant - Hartinie Marbawi; Siti Nadhirah Sidi Ahmad; Nur Shaheera Baharudin; Jualang Azlan Gansau (e-VIBS, Faculty of Science and Natural Resources, 2016)
Cynometra cauliflora or known as ‘Nam-Nam’ is an underutilized medicinal plant of Malaysia. In this study, embryo from matured seed of C. cauliflora was cultured on the Murashige & Skoog medium containing 0.5 μM BAP. Embryo germination achieved up to 100% and produced an average of 8.8±2.0 shoot buds per explant and 1.7±1.5 leaves after eight weeks. Stem and shoot tips explants from in vitro plantlets were further treated with 5, 10 and 15µM Thidiazuron (TDZ) for regeneration capacity. Stem explant responded 100% to callus induction after two weeks of culture on medium containing 10 μM and 15μM TDZ. Meanwhile, shoot tip explant recorded only 12.11±0.54% to callus induction after 6 weeks of culture on medium containing 5μM TDZ. Stem explant remain at calli stages until the end of study, while shoot tips undergo shoot regeneration by inducing up to 54.45±9.27% shoots production with an average of 3.00±1.00 shoots per explant. Browning phenomenon was severely observed on the culture throughout this study. Therefore, the addition of activated charcoal to the culture medium will be beneficial to eliminate phenolics accumulation.